Health and nutrition of Orang Asli (Che Wong) at Krau Wildlife Reserve, Pahang – a descriptive study - Karppaya, Haemamalar; Mohd Shariff , Zalilah; Ngan, W. L.; Azman, Neng Azhanie (Nutrition Society of Malaysia, 2008)
This study was conducted to determine the nutritional status of Orang Asli (Che Wong) men, women and children. Through purposive sampling, 29 households consisting of 29 men, 28 women, and 20 children (10 female and 10 male) were chosen. Demographic and socioeconomic information were collected using structured questionnaire. Men and women were measured for height, weight, blood pressure and waist circumference while weight and height was measured for children. Mean age for men, women and children were 39.89±17.09 years, 33.7±16.08 years, and 3.25±1.33 years respectively. Only 6.9% of men and 14.3% of women completed 3 years of primary school education. The average household income was RM 261.56±254.40. Mean Body Mass Index (BMI) for men was 21.83±3.40 (underweight: 13.8%, normal: 72.4%, overweight: 10.3%, and obese: 3.3%). Mean Body Mass Index (BMI) for women was 28.6±4.05 (underweight: 23.3%, normal weight: 46.3%, and overweight: 26.7%). The mean circumference for men was 74.43±6.09cm and for women, it was 73.92±6.80 cm. However, caution should be exercised when interpreting the BMI results when none of them had waist circumference more than 102 cm (men) and 88 cm (women). About 10.3% of the men and 10.7% of women had blood pressure of more than 130/85 mmHg. The prevalence of underweight, stunting and wasting of children was 45%, 35% and 30% respectively. Food frequency questionnaire (FFQ) consisting of seven food groups (cereals, meats, fish, fruits, vegetables, dairy products and drinks) was used to determine the dietary diversity score. The minimum score was 0 and the maximum score was 37. Mean total score for men was 9.46±3.70 (maximum score of 18) and for women, it was 9.48 ± 4.63 (maximum score of 21). Food patterns for both male and female were similar whereby fruits and milk groups were the least consumed. In conclusion, further research should be conducted in the Che Wong community to determine the association between food intake and nutritional status of Orang Asli.